2016
DOI: 10.1080/08958378.2016.1210703
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to waterpipe smoke induces renal functional and oxidative biomarkers variations in mice

Abstract: In conclusion, chronic waterpipe smoke affects the kidney parameter and antioxidant markers, therefore affecting its functionality of detoxifying and removal of poisonous material from the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…We found that C57BL/6J strain was more susceptible to acute WPS-induced oxidative stress response among the two strains. Our results are consistent with earlier findings that WPS induces oxidative stress by generation of ROS and depletion in GSH levels and increase in GSSG levels in several organs (Nemmar et al 2013;Ali et al 2017;Alzoubi et al 2015;Rababa'h et al 2016). It could also be possible due to the formation of GSH conjugates or rapid consumption of GSH during the breakdown of free radicals induced by WPS, thereby altering GSH redox system (Rahman and MacNee 1999).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that C57BL/6J strain was more susceptible to acute WPS-induced oxidative stress response among the two strains. Our results are consistent with earlier findings that WPS induces oxidative stress by generation of ROS and depletion in GSH levels and increase in GSSG levels in several organs (Nemmar et al 2013;Ali et al 2017;Alzoubi et al 2015;Rababa'h et al 2016). It could also be possible due to the formation of GSH conjugates or rapid consumption of GSH during the breakdown of free radicals induced by WPS, thereby altering GSH redox system (Rahman and MacNee 1999).…”
Section: Discussionsupporting
confidence: 94%
“…; Rababa'h et al. ). It could also be possible due to the formation of GSH conjugates or rapid consumption of GSH during the breakdown of free radicals induced by WPS, thereby altering GSH redox system (Rahman and MacNee ).…”
Section: Discussionmentioning
confidence: 97%
“…Together, these SOD enzymes scavenge superoxide anion into molecular oxygen and hydrogen peroxide, then CAT and GPx reduce hydrogen peroxide, thus preventing production of highly toxic hydroxyl radical [64]. Growing evidence indicates that cigarette smoking or CSE significantly decrease the activities of anti-oxidative enzymes both in vitro and in vivo researches [65,66]. In the present study, our results displayed a significant reduction in activities of SOD1, SOD2, CAT and total GPx in CSE rat placentas, however, the decreased activities of the anti-oxidative enzymes were improved with NaHS application.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have reported negative health effects of CS on the kidney (Xia et al, 2017), little is known about the potential adverse impact of WPS exposure on the kidney. It has been recently reported that exposure to WPS causes oxidative stress in the kidney (Rababa'h et al, 2016). However, the mechanisms underlying this effect remain unknown.…”
Section: Introductionmentioning
confidence: 99%